The Effect of Ultra-Fast Heating on the Microstructure, Grain Size and Texture Evolution of a Commercial Low-C, Medium-Mn Dp Steel - Hernandez-Duran, E (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The effect of ultra-fast heating on the microstructures of steel has been thoroughly studied over the last year as it imposes a suitable alternative for the production of ultra high strength steel grades. Rapid reheating followed by quenching leads to fine-grained mixed microstructures. This way the desirable strength/ductility ratio can be achieved while the use of costly alloying elements is significantly reduced. The current work focuses on the effect of ultra-fast heating on commercial dual phase grades for use in the automotive industry. Here, a cold-rolled, low-carbon, medium-manganese steel was treated with a rapid heating rate of 780 °C/s to an intercritical peak temperature (760 °C), followed by subsequent quenching. For comparison, a conventionally heated sample was studied with a heating rate of 10 °C/s. The initial microstructure of both sets of samples consisted of ferrite, pearlite and martensite. It is found that the very short heating time impedes the dissolution of cementite and leads to an interface-controlled α → γ transformation. The undissolved cementite affects the grain size of the parent austenite grains and of the microstructural constituents after quenching. The final microstructure consists of ferrite and martensite in a 4/1 ratio, undissolved cementite and traces of austenite while the presence of bainite is possible. Finally, it is shown that the texture is not strongly affected during ultra-fast heating, and the recovery and recrystallization of ferrite are taking place simultaneously with the α → γ transformation. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.